2018
DOI: 10.4155/fsoa-2017-0144
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Glycemic Control Outcomes Among Patients with Coexisting Pancreatic Cancer and Diabetes Mellitus

Abstract: Aim:We aimed to determine the effect of diabetes mellitus (DM) on survival in pancreatic cancer and effects of pancreatic cancer on glycemic control in DM.Materials & methods:Patients with pancreatic cancer from 2007 to 2015, with and without DM, were matched 1:1. We compared characteristics between the groups and assessed 2-year survival with Kaplan–Meier analysis.Results:In patients with DM, hemoglobin A1c decreased significantly over time (p = 0.01). In survival analysis, 2-year overall survival estimates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…For patients and healthcare providers responsible for management of DM, it is encouraging that glycemic control did not worsen, at least over the year timeframe analyzed here. This observation is similar to that of our previous analyses of other solid organ malignancies [15][16][17][18]. Although HbA 1c was available for only about half of the DM patients, it did not increase over 12 months.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For patients and healthcare providers responsible for management of DM, it is encouraging that glycemic control did not worsen, at least over the year timeframe analyzed here. This observation is similar to that of our previous analyses of other solid organ malignancies [15][16][17][18]. Although HbA 1c was available for only about half of the DM patients, it did not increase over 12 months.…”
Section: Discussionsupporting
confidence: 90%
“…The statistical analyses conducted were similar to those used for our previous studies [15][16][17][18]. Patient demographic and clinical characteristics were compared between patients with colorectal cancer with and without DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case–control studies of patients at a large cancer institute in the southwestern USA have shown that diabetes does not worsen survival for patients with solid organ cancers and that solid organ cancers do not worsen glycemic control. We have studied this relationship in pancreatic cancer [ 15 ], gastroesophageal cancer [ 16 ], lung cancer [ 17 ], breast cancer [ 18 ], prostate cancer [ 15 ], colorectal cancer [ 19 ] and melanoma [ 20 ]. Gastroesophageal cancer was the only cancer in which a greater risk of death was seen in patients with than without diabetes [ 16 ].…”
mentioning
confidence: 99%